T lymphocytes and macrophages in the intestinal tissues of dogs infected with Leishmania infantum - Silva, Diogo Tiago da [UNESP]; Alves, Maria Luana [UNESP]; Spada, Júlio Cesar Pereira [UNESP]; Silva, Aline Cristine da [UNESP]; Silveira, Rita de Cássia Viveiros da [UNESP]; Oliveira, Trícia Maria Ferreira de Sousa; Starke-Buzetti, Wilma Aparecida [UNESP] (FapUNIFESP (SciELO), 2017)
This study was about a semi-quantitative analysis of T lymphocytes (CD4+ and CD8+, FoxP3+ regulatory T cells), and macrophages in the gut wall of dogs naturally infected with Leishmania infantum. Thirteen dogs were divided into three groups: group 1 (G1, n=5), dogs with canine visceral leishmaniasis (CVL) and infected with L. infantum amastigotes in the intestine; group 2 (G2, n=5), dogs with CVL but without intestinal amastigotes; and group 3 (G3, n=3), uninfected dogs (control group). There was no significant difference (p ≥ 0.05) on CD4+ and Treg cell numbers among the groups, whereas the levels of CD8+ T cells and macrophages were significantly higher in dogs from G1 group than in G2 and G3 (p ≤ 0.05), especially in intestinal segments with high parasite burden. Parasite burden correlated positively with levels of CD8+ T cells and macrophages (p ≤ 0.05), but was inversely correlated to levels of CD4+ T lymphocytes and FoxP3+ Treg cells. In conclusion, in the intestine of dogs with CVL, the increase of CD8+ T cells and macrophages population associated with high parasite burdens, but no changes of CD4+ T cells and FoxP3+ Treg cells suggest a possible immunoregulation by the parasite not dependent on Treg cells.
Linfócitos T e macrófagos nos tecidos intestinais de cães infectados com Leishmania infantum
Keywords: Canine visceral leishmaniasis; Intestinal tract; Macrophages; T lymphocytes